Transformational Leadership in Vocational Education: School Principal Strategies for Teacher Performance Improvement - Ujang Permana; Hanafiah Hanafiah; R. Supyan Sauri; Emay Mastiani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Teacher performance plays a crucial role in achieving educational success and is significantly influenced by the leadership and management of school principals. This study investigates how principal management practices contribute to improving teacher performance in vocational high schools. This qualitative descriptive study employed a case study approach and was conducted at two vocational high schools in Majalengka. Participants were selected using purposive and snowball sampling methods, involving principals, teachers, and students. Data were collected through interviews, observations, and document analysis. The data analysis process included data reduction, data display, and verification, while data validity was ensured through credibility, transferability, dependability, and confirmability measures. Findings reveal that effective principal planning is evident through the development of school vision, mission, goals, strategic and operational plans, and a positive working climate. Organizational efforts include establishing a clear structure, curriculum planning, co-curricular programs, teaching schedules, and job descriptions. Implementation is carried out via activities such as socialization, in-house training (IHT), curriculum workshops, lesson plan (RPP) training, industrial work practice programs, and discipline enforcement. Evaluation of principal leadership is conducted by monitoring teacher attendance, assessing understanding of school policies, and observing classroom practices. Principals play a pivotal role in enhancing teacher performance through strategic planning, structured organization, effective implementation, and continuous evaluation. These efforts collectively contribute to improved teaching quality and educational outcomes in vocational schools.